2012
DOI: 10.1080/08327823.2012.11689838
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Effect of the Magnetic Field Component of the Microwave Radiation on Aqueous Electrolyte Solutions

Abstract: The heating characteristics of aqueous electrolyte solutions (NaCl, KCl, CaCl2, NaBF4, and NaBr) of varying concentrations in ultrapure water by 2.45 GHz microwave radiation from a single-mode resonance microwave device and a semiconductor microwave generator were examined under conditions where the electric field (E-field) was dominant and where the magnetic field (H-field) dominated. Although magnetic field heating is not generally used in microwave chemistry, the electrolyte solutions were heated almost ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…It was reported that heating rates of the electrolyte solutions (NaCl, KCl, CaCl 2 , NaBF 4 , and NaBr) were far more significant than that of same-volume ultrapure water when they are heated in the same microwave conditions [42]. For the aqueous electrolyte solutions, both dipolar polarization and conductive mechanisms contribute to the heating effect.…”
Section: Microwave Heating Theory and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that heating rates of the electrolyte solutions (NaCl, KCl, CaCl 2 , NaBF 4 , and NaBr) were far more significant than that of same-volume ultrapure water when they are heated in the same microwave conditions [42]. For the aqueous electrolyte solutions, both dipolar polarization and conductive mechanisms contribute to the heating effect.…”
Section: Microwave Heating Theory and Mechanismsmentioning
confidence: 99%
“…Magnetic resonance losses are primarily induced by domain wall resonance and electron spin resonance [42,46,57]. In the literature, residual losses were also used to represent the losses originating from various magnetic relaxations and resonances which occurs mainly in two ways, as rotational resonance and as domain wall resonance [55,58].…”
Section: Microwave Heating Theory and Mechanismsmentioning
confidence: 99%
“…Therefore, emulsion size is an important factor that determines the heating efficiency by microwave. On the other hand, the microwave-heating rate can be remarkably changed by the addition of inorganic ions as impurities 10 .…”
Section: Conduction Loss Heatingmentioning
confidence: 99%
“…The de-emulsification process was prevented by higher pH and salt concentrations; these conditions contribute to an increase in solution conductivity. Therefore, since the penetration depth of microwave fell, heating efficiency decreased 10 .…”
Section: 3mentioning
confidence: 99%
“…This effect has been explained with a Joule loss resulting from an eddy current induced by the microwave's alternating magnetic eld. 24 In this paper, the interference of the polyol synthesis of silver-containing nanoparticles by the microwave E-eld and H-eld was investigated. To investigate the eld effects the synthesis has been performed in solutions containing Ag ions and additionally diamagnetic or paramagnetic (Ni 2+ ) ions.…”
Section: -23mentioning
confidence: 99%